Take the 2-minute tour ×
Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

This might be an insanely dumb question but I just spent about four hours figuring out how to show that for $0<a<1$ and $N\leq b<N+1$, the following holds

$$\sum_{n=1}^{N}f(n)=\int_{a}^{b}f(x)dx+\int_{a}^{b}f'(x)\langle x\rangle dx+f(a)\langle a\rangle-f(b)\langle b\rangle$$ where $\langle x\rangle$ is the fractional part of $x$. My proof goes like this:

Let $$E=\sum_{n=1}^{N}f(n)-\int_{a}^{b}f(x)dx$$ so that $$\sum_{n=1}^{N}f(n)=\int_{a}^{b}f(x)dx+E$$ Skipping over some details, we can write $E=\int_{a}^{b}f(x)d\alpha-\int_{a}^{b}f(x)dx$ where $\alpha(x)=\sum_{a<n\leq b}H(x-n)$ where $H$ is the Heaviside step function. It just so happens that when we are summing over 1 to N this is the floor function, so after some rearranging and integrating by parts I get $$E = -\left(f(b)(b-\lfloor b\rfloor)-f(a)(a-\lfloor a\rfloor)-\int_{a}^{b}f'(x)(x-\lfloor x\rfloor)dx\right) = -\left(f(b)\langle b\rangle-f(a)\langle a\rangle-\int_{a}^{b}f'(x)\langle x\rangle dx\right) = \int_{a}^{b}f'(x)\langle x\rangle dx+f(a)\langle a\rangle-f(b)\langle b\rangle$$ and the result follows.

Unfortunately my homework is to show that $$\sum_{a<n\leq b}f(n)=\int_{a}^{b}f(x)dx+\int_{a}^{b}f'(x)\langle x\rangle dx+f(a)\langle a\rangle-f(b)\langle b\rangle$$Is there a nice way to show that the first implies the second without rewriting the entire proof? The issue is the bold part of the proof—if we're not summing from 1 to n but rather, say, m to n then $\alpha$ doesn't turn into the floor function. I can't think of a simple way to generalize this—maybe I'm just not seeing something obvious.

share|improve this question
1  
$\displaystyle\sum_{a < n \leq b} f(n) = \sum_{n = 1}^{b} f(n) - \sum_{n = 1}^{a} f(n)$ ? –  Pedro Jan 31 '13 at 23:12
    
@Pedro ugh yes I just thought of that. I had been trying to do something much more complicated involving defining a new function which was a horizontal translation of $f$ and it wasn't working. –  crf Jan 31 '13 at 23:13
add comment

1 Answer

up vote 1 down vote accepted

For the sake of completeness, here is the answer to my own question. Letting $m$ be the least integer greater than $a$ and $M$ be the greatest integer less than or equal to $b$ and recalling that $$\sum_{a<n\leq b}f(n)=\sum_{n=1}^{M}f(n)-\sum_{n=1}^{m-1}f(n)$$ we obtain $$\sum_{a<n\leq b}f(n) = \sum_{n=1}^{M}f(n)-\sum_{n=1}^{m-1}f(n) = \int_{1}^{b}f(x)dx+\int_{1}^{b}f'(x)\langle x\rangle dx+f(1)-f(b)\langle b\rangle - \int_{1}^{a}f(x)dx-\int_{1}^{a}f'(x)\langle x\rangle dx-f(1)+f(a)\langle a\rangle = \int_{a}^{b}f(x)dx+\int_{a}^{b}f(x)\langle x\rangle dx+f(a)\langle a\rangle-f(b)\langle b\rangle $$

share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.